2022
DOI: 10.3390/ijms23052771
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Nanoparticles and Composite Hydrogel Systems for Delivery of Peptide Antibiotics

Abstract: The growing number of drug-resistant pathogenic bacteria poses a global threat to human health. For this reason, the search for ways to enhance the antibacterial activity of existing antibiotics is now an urgent medical task. The aim of this study was to develop novel delivery systems for polymyxins to improve their antimicrobial properties against various infections. For this, hybrid core–shell nanoparticles, consisting of silver core and a poly(glutamic acid) shell capable of polymyxin binding, were develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Recent research revealed that the hydrogel with biocompatibility, controllable modulus, and structure adjustable was considered as a promising the wound dressings for loading PMB [ 13 15 ]. In particular, the gelatin methacryloyl (GelMA), a semi-solid hydrogel, has received a great deal of attention owing to its biocompatibility, low immunogenicity, similarity to native tissue, and bio-degradability.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research revealed that the hydrogel with biocompatibility, controllable modulus, and structure adjustable was considered as a promising the wound dressings for loading PMB [ 13 15 ]. In particular, the gelatin methacryloyl (GelMA), a semi-solid hydrogel, has received a great deal of attention owing to its biocompatibility, low immunogenicity, similarity to native tissue, and bio-degradability.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, three negatively charged polymers and a neutral glycopolymer were selected. Recently, copolymer of L-glutamic acid and L-phenylalanine (P(Glu-co-Phe)) [28] and poly(α,L-glutamic acid) (PGlu) [29] were tested as PMX B and E delivery systems, in which positively charged PMXs were bound to negatively charged polymers due to polyelectrolyte interactions. Here, PMX B was conjugated with P(Glu-co-Phe) and PGlu to compare the properties of physically loaded and covalently bound PMX B.…”
Section: Introductionmentioning
confidence: 99%
“…The research was focused on the antibacterial properties and biocompatibility of hydrogel to treat a full-thickness wound [14]. Some researchers were loading PMB into various hydrogels by entrapping mesh size and electrostatic interactions [18][19][20]. However, non-covalent encapsulation of PMB may allow for rapid release of the drug in the trabeculae, leading to instantaneous and extremely high local PMB concentrations triggering side effects.…”
Section: Introductionmentioning
confidence: 99%